Treatment de‐escalation in HPV‐positive oropharyngeal carcinoma: Ongoing trials, critical issues and perspectives. Issue 7 (4th April 2014) - Mirghani, H.; Amen, F.; Blanchard, P.; Moreau, F.; Guigay, J.; Hartl, D.M.; Lacau St Guily, J.
<x xml:space="preserve">Abstract</x> Due to the generally poor prognosis of head and neck squamous cell carcinoma (HNSCC), treatment has been intensified, these last decades, leading to an increase of serious side effects. High‐risk human papillomavirus (HR‐HPV) infection has been recently etiologically linked to a subset of oropharyngeal squamous cell carcinoma (OPSCC), which is on the increase. These tumors are different, at the clinical and molecular level, when compared to tumors caused by traditional risk factors. Additionally, their prognosis is much more favorable which has led the medical community to consider new treatment strategies. Indeed, it is possible that less intensive treatment regimens could achieve similar efficacy with less toxicity and improved quality of life. Several clinical trials, investigating different ways to de‐escalate treatment, are currently ongoing. In this article, we review these main approaches, discuss the rationale behind them and the issues raised by treatment de‐escalation in HPV‐positive OPSCC.